Human Rights and Civil Society in Global Context - Candra Caymuna, Carara (Konsultan Surya Buanan, 2024)
This research aims to explore the role of civil society organizations in promoting gender equality for women within the context of human rights. The research methodology applied in this study is a systematic literature review, utilizing 517 scholarly articles sourced from the Scopus database. The article review process employs the Vosviewer application. The study highlights how these organizations mobilize resources and advocate for policy changes that significantly strengthen the protection and empowerment of women, as well as respond to specific challenges faced by women. The results of this research contribute to the development of knowledge, particularly in the field of governance, by providing insights into civil society's role in advocating for women's rights. The findings are valuable for policymakers and practitioners in the realms of human rights and gender equality. However, a limitation of the study is that the articles used are solely derived from the Scopus database, limiting the comprehensive portrayal of human rights and civil society.